2016
DOI: 10.1002/jbt.21781
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression Determination of p38 MAPK from the Liver and Kidney of Silver Carp

Abstract: The sequence of p38MAPK in silver carp (Hm-p38a) was cloned and sequenced. Additionally, the acute toxicity of crude microcystins (MCs) on silver carp and induction expression of Hm-p38a by MCs exposure were also determined in this study. The results reveal that the length of Hm-p38a is 2418 bp and it contains a 1086 bp open reading frame. Hm-p38a could encode 361 amino acids. Sequence analysis indicates that Hm-p38a contains the conserved structures of Thr-Gly-Tyr motif and substrate binding site Ala-Thr-Arg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In previous studies, the p38 MAPK pathway in grouper was shown to be activated by infection with Singapore grouper iridovirus (SGIV) (Cai et al., 2011; Huang et al., 2011). Other studies have shown that bacterial and viral infection can activate the p38 MAPK signalling pathway in various fish (Li et al., 2016; Umasuthan et al., 2015; Zhu, et al., 2014a). In this study, both gene and protein expressions of p38 MAPK were significantly increased in Nile tilapia and hybrid tilapia after S. agalactiae infection, and the abundance of the p38 MAPK protein increased in a time‐dependent manner.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In previous studies, the p38 MAPK pathway in grouper was shown to be activated by infection with Singapore grouper iridovirus (SGIV) (Cai et al., 2011; Huang et al., 2011). Other studies have shown that bacterial and viral infection can activate the p38 MAPK signalling pathway in various fish (Li et al., 2016; Umasuthan et al., 2015; Zhu, et al., 2014a). In this study, both gene and protein expressions of p38 MAPK were significantly increased in Nile tilapia and hybrid tilapia after S. agalactiae infection, and the abundance of the p38 MAPK protein increased in a time‐dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…However, research on the roles of p38 MAPKs in the pathogenesis of fish is limited. To date, p38 MAPKs have been detected in carp (Hashimoto et al., 2000), grass carp (Li et al., 2015a), silver carp (Li et al., 2016; Ma et al., 2018), zebrafish (Krens et al., 2006), Atlantic salmon (Hansen & Jørgensen, 2007), orange‐spotted grouper (Cai et al., 2011), amphioxus (Zhu et al., 2014a), blunt snout bream (Zhang et al., 2018) and large yellow croaker (Li et al., 2019b). A few kinds of parasites, bacteria and viruses could active p38 MAPK pathway, such as Aeromonas hydrophila , Microcystins and Singapore grouper iridovirus .…”
Section: Introductionmentioning
confidence: 99%
“…Early in 1999, Toivola and Eriksson hypothesized that MC might promote MAPK signaling pathways and MAPK be a key pathway for MCs-toxicity [ 44 ]. In recent years, more and more studies confirmed that MC-hepatotoxicity was mediated by MAPK pathway due to PP2A inhibition by MC [ 45 , 46 , 47 , 48 ]. In the present study, considerable target genes of aberrant miRNAs induce by MC-LR were also enriched to MAPK pathway, suggesting that the pathway may play a key role in MC-LR cytotoxicity on HepG2 cells via the negative regulation of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The genes utilized to validate the RNA-seq data were the members of overlapping DEGs from CK versus T1, CK versus T2, and CK versus T3, and their primers were built using Primer 6. B-actin served as the control gene (Li et al, 2013;Li et al, 2016). qPCR was performed on samples that were not related to those utilized for RNA-seq.…”
Section: Real Time Quantitative Pcr (Rt-qpcr) Analysismentioning
confidence: 99%